Pembudayaan Literasi Numerasi dalam Kegiatan Inti Pembelajaran Matematika di Sekolah Menengah Pertama - Rahmayanti, Danica Zerlinda; Sutama (JURNAL RISET PEMBELAJARAN MATEMATIKA SEKOLAH, 2022)
Numerical literacy skills are needed in all aspects of life, both in education, work and society. Numerical literacy continues to grow so that it requires humans to continue to adapt in various aspects of education. Numerical literacy is seen as an evolution and is used as a foundation for the development of education in Indonesia so that the cultivation of numeracy literacy is very important. The research objectives in this article are twofold. 1) Describe controlled training of numeracy literacy culture groups in core activities. 2) Describe the independent training of numeracy literacy culture in core activities. The type of research used by the researcher is qualitative research. This research was carried out on students of SMP Negeri 1 Matesih. The research was conducted from May to September 2022. The research subjects were seventh grade students of SMP Negeri 1 Matesih. Data collection techniques were carried out by collecting documents, collecting theories, interviewing mathematics teachers, direct observation and giving questionnaires. Data validity by triangulation. Data analysis techniques using two ways, namely data reduction, data presentation and conclusions. There are two research results in this article. 1) Controlled training of numeracy literacy culture groups in core activities is carried out with open discussions during mathematics learning. 2) Independent training of numeracy literacy culture in core activities is carried out by giving independent assignments as an exercise. The teacher gives several tasks to support the level of students' understanding of a material.